A randomized trial of narrow band imaging for performing airway mucosal biopsy in pulmonary sarcoidosis (NABS) - Rathi, Kritarth; Dogra, Pooja; Agarwal, Ritesh; Singh Sehgal, Inderpaul; Muthu, Valliappan; Thurai Prasad, Kuruswamy; Aggarwal, Ashutosh Nath; Bal, Amanjit; Gupta, Nalini; Dhooria, Sahajal (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: Data suggest that narrow band imaging (NBI) highlights airway mucosal nodules better than white light bronchoscopy (WLB) in sarcoidosis. No randomized trial has compared the diagnostic yield of endobronchial biopsy (EBB) performed using NBI versus WLB.Methods: We performed an investigator-initiated single-center, parallel-arm, randomized trial. Consecutive subjects ≥18 years of age with clinico-radiologic presentation consistent with sarcoidosis were randomised 1:1 to undergo EBB using NBI plus WLB (intervention) or WLB (control).Outcomes: The primary outcome was the diagnostic yield of EBB defined by finding of granulomas on pathologic examination in subjects with final diagnosed with sarcoidosis. The secondary outcomes included procedure duration and complications.Results: We included 150 (mean age, 43.1 years; 53.3% men) subjects; 75 each were assigned to either study group. Sarcoidosis was diagnosed in 126/150 subjects (66 and 60 in the NBI plus WLB and WLB groups, respectively). There was no difference (p=0.53) in the diagnostic yield of EBB between the NBI plus WLB (25/66, 37.9%) and the WLB (26/60, 43.3%) groups. Transbronchial lung biopsy and endobronchial ultrasound-guided transbronchial needle aspiration yielded granulomas in 69 of 115 (60%) and 68 of 98 (69.4%) subjects, who underwent these additional procedures, respectively. In 11 of the 14 (78.6%) cases, where WLB demonstrated airway nodules, NBI enhanced visualization. Moreover, it identified nodules in five additional cases. There were no between-group differences in the procedure duration or complications.Conclusions: The use of NBI did not improve the yield of EBB in patients with sarcoidosis. Additional research is warranted. (Clinicaltrials.gov: NCT05311150)